Faktor Risiko Terjadinya Pneumonia Oleh Carbapenem-Resistant Organism (Cro) Pada Bayi Dan Anak di Ruang Perawatan Intensif : Sebuah studi di RSUP Dr. Kariadi - Arkhaesi, Nahwa; Istanti, Yusrina; Saputra, Mohammad Supriatna Toto; Priyatiningsih, Dewi Ratih; Soleha, Indah; Salsabila, Salma Tyas (RSUP Dr. Kariadi, 2026)
BACKGROUND: Inappropriate antibiotic use has led to bacterial resistance, including carbapenem-resistant organisms (CROs), which cause severe infections in neonatal intensive care unit (NICU) and pediatric intensive care unit (PICU) patients. CRO infections are associated with high morbidity and mortality rates, with limited treatment options. Risk factors such as prolonged hospitalization, broad-spectrum antibiotic use, invasive procedures, and prior infections contribute to these cases. This study is the first in Indonesia to specifically examine CRO pneumonia risk factors in NICU and PICU children. OBJECTIVES: This study aimed to analyze the risk factors for pneumonia caused by carbapenem-resistant organisms (CROs) in children in the pediatric and neonatal intensive care unit. METHODS: This case-control study was conducted in neonatal intensive care unit (NICU) and Pediatric Intensive Care Unit (PICU) of Dr. Kariadi Hospital, Semarang, using medical records of patients admitted between November 2022 and October 2024. This study analyzed the relationship between various risk factors, including hospitalization duration, antibiotic use, mechanical ventilation, catheterization, prior surgery, and bacterial infection history, with CRO pneumonia in NICU and PICU patients. RESULTS: This case-control study in NICU and PICU on 87 pediatric pneumonia patients found that 55.2% had CRO pneumonia. Multivariate analysis revealed that carbapenem use for >7 days (p = 0.049), mechanical ventilation (p = 0.044), and urinary catheterization (p = 0.020) were independent risk factors for CRO pneumonia. CONCLUSION: CRO infections in NICU and PICU patients are highly prevalent, with prolonged carbapenem use, mechanical ventilation, and urinary catheterization as independent risk factors for CRO pneumonia.